2019
DOI: 10.1002/cche.10126
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, physicochemical, and functional quality of beetroot (Beta vulgarisL.) incorporated Asian noodles

Abstract: Background and objectives:Noodles are staple food for many Asian countries as these are easy to prepare, economic, and convenient, thus gaining popularity throughout world. However, wheat flour-based noodles are deficient in essential nutrients. So, the present study was planned to investigate the potential of beetroot pulp (0%, 10%, 20%, 30%, and 40%) as a component in noodle manufacturing to improve the nutritional status. Phytochemical analysis, cooking qualities, pasting properties, color, and sensory prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…Consumption of noodles is very popular in the Asian diet, and as a major wheat food product, noodles have a very high demand (Chhikara, Kushwaha, Jaglan, Sharma, & Panghal, ). In contrast to Japanese, white salt noodles (WSN), udon or spaghetti, the type of WSN consumed in China is different owing to the unique wheat grain composition (Huang & Lai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of noodles is very popular in the Asian diet, and as a major wheat food product, noodles have a very high demand (Chhikara, Kushwaha, Jaglan, Sharma, & Panghal, ). In contrast to Japanese, white salt noodles (WSN), udon or spaghetti, the type of WSN consumed in China is different owing to the unique wheat grain composition (Huang & Lai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies on beetroot pulp‐added noodles (Chhikara, Kushwaha, Jaglan, Sharma, & Panghal, ) and black rice bran‐added noodles (Kong et al, ) observed the effect of polyphenolic compounds on color characteristics. This could be due to formation of melanoids during processing as well as reaction of polyphenol oxidase with phenols leading to increased antioxidant activity (Chhikara et al, ).…”
Section: Resultsmentioning
confidence: 92%
“…Progressive decrease in lightness value was observed from 51.98 to 46.76 with increase in level of beetroot powder. A reduction in L⃰ value of noodles showed low luminosity, brightness and subsequently darker appearance of noodles (Chhikara et al, 2018). The a* value of control noodle was 1.13 and those of beetroot powder was increased from 5.12 to 9.47, showing more reddish colour than the control.…”
Section: Statistical Analysesmentioning
confidence: 92%
“…It has been observed that short cooking time with less soluble solid are the desirable quality of a good noodle (Sirichokworrakit et al,2015). Chhikara et al, (2018) explained that the cooking loss was as a result of weakening or disruption of the protein-starch matrix and an uneven spreading of water within the matrix due to the presence of beetroot powder. Due to this, more solid were leached out from noodles into the cooking water.…”
Section: Table 4: Swelling Power the Cooking Loss And The Colour Anamentioning
confidence: 99%